ANALISIS PESAN MORAL DALAM BUKU CERITA PERTOLONGAN KAKAK TUA SEBAGAI MEDIA PENANAMAN NILAI KEBERANIAN PADA ANAK USIA DINI - Asthania, - (2021)
The value of courage at an early childhood cannot be possessed naturally, but needs to be instilled and pursued by parents, caregivers, or AUD educators. So far, the most frequently used method of inculcating values of courage in early childhood is story and storytelling. In fact, in PAUD institutions, there are still many learnings that apply storytelling methods through media that children don't like, as a result children tend to feel bored and find it difficult to digest the contents of the story. The purpose of this study is to examine the contents of the story book entitled "The Help Of The Cockatoo" to examine whether storie are suitable to be used as learning media for early childhood, especially as a medium for inculcating values of courage in early childhood. This study uses an analytical method with a qualitative approach. The results of the analysis of the story book "The Help Of The Cockatoo", obtained several findings, namely the story of "The Help Of The Cockatoo" with light language and simple sentence structure, sequential storyline, so that it is easy for early childhood to understand. The character of the story and the moral message contained in harmony with the values of courage of AUD. And declared in accordance with the criteria to be used as learning media for early childhood, especially in activities related to instilling the value of courage in AUD. Keywords: The Value of Courage, Early Childhood, Moral Messages, Storybook